PROBLEMS FACED BY MANAGEMENT BUSSINESS HOSPITALITY STUDENTS IN SPEAKING ENGLISH AND THEIR STRATEGIES TO IMPROVE THEM - Rai Antara, I Made Agung; Yunik Anggreni, Ni Putu (Jurnal Manajemen Pelayanan Hotel, 2022)
This study aims to analyse management business and hospitality students’ difficulties in speaking and their strategies to improve them. This study was qualitative research using descriptive qualitative analysis. There were 10 students used as respondents. They were interviewed regarding their difficulties encountered in speaking English and their tactics to solve the problems. The research showed that there some difficulties faced by students such as lack of confidence, pronunciation, vocabularies, and grammar. However, they also implement some strategies to enhance their speaking skill such as memorize vocabularies, watch video in English, listen English song, read article in twitter, practice speaking in front of mirror, watch youtube, tiktok, learn from people who are smarter from them and use application such as hilokal to interact with people from other countries. It is recommended that the emphasis of teaching and learning in speaking should focus more on how to build the students’ self confidence so that they will have the confidence to interact with their friends and teachers. Keywords: Speaking, grammar, pronunciation, vocabularies, confidence.